MAMA-AFRICA REPRESENTATIONS IN THE MOZAMBICAN AND AFRO-BRAZILIAN POETRIES - Donizeth Santos (Abril, 2012)
Through the analysis of poems, “Sangue negro”, by the Mozambican poet Noémia de Sousa, “Regressão” and “Elo”, by the Afro-Brazilian poet Oliveira Silveira, the article shows that Mother-Africa is represented in a Mozambican poetry as the biological black mother, the nation and the African continent, while in the Afro-Brazilian, besides being the progenitor of the black mankind, the African continent, is also the promised land, the lost paradise.